A literature review and survey of childhood pneumonia etiology studies: 2000-2010. - Gilani, Z; Kwong, Y; Levine, O; Deloria-Knoll, M; Scott, J; O'Brien, K; Feikin, DR (2012)
The Pneumonia Etiology Research for Child Health (PERCH) project is the largest multicountry etiology study of childhood pneumonia since the Board on Science and Technology in International Development studies of the 1980s. However, it is not the only recent or ongoing pneumonia etiology study, and even with seven sites, it cannot capture all epidemiologic settings in the developing world. Funding providers, researchers and policymakers rely on the best available evidence to strategically plan programs, new research directions and interventions. We aimed to describe the current landscape of recent pneumonia etiology studies in children under 5 years of age in the developed and developing world, as ascertained by a literature review of relevant studies with data since the year 2000 and a survey of researchers in the field of childhood pneumonia. We collected information on the study population, study design, case definitions, laboratory samples and methods and identified pathogens. A literature review identified 88 studies with child pneumonia etiology results. As of June 2010, our survey of researchers identified an additional 65 ongoing and recently completed child pneumonia etiology studies. This demonstrates the broad existing context into which the PERCH study must be placed. However, the landscape analysis also reveals a multiplicity of case definitions, levels of clinician involvement, facility types, specimen collection, and laboratory techniques. It reinforces the need for the standardization of methods and analyses for present and future pneumonia etiology studies in order to optimize their cumulative potential to accurately describe the microbial causes of childhood pneumonia.